Ultra-Low Temperature Coefficient of Capacitance (Tcc) of the SrSnO3-Based Electrical Components - Abdul-Majeed Azad; Toh Yen Pang; Mohammad A. Alim (Active and Passive Electronic Components)
The perovskite-structured SrSnO3 possessing steady capacitance over the temperature range between 27°C and 300°C in a frequency domain spanning nearly four decades has been evaluated. The samples investigated in this study were synthesized by using solid-state reaction (SSR) and self-heat-sustained (SHS) techniques. These samples were sintered at a temperature (T ) ranging between 1200°C and 1600°C with a soak-time (t) ranging between 2 h and 60 h. The ac immittance (impedance or admittance) measurements were conducted on these sintered bodies in the frequency range 5Hz to 13 MHz. These ac electrical data were found to exhibit relaxation in more than one complex plane formalisms in a simultaneous manner. The magnitude of the terminal capacitance was found to be in a narrow window of 3 pF to 6 pF possessing very weak temperature dependence. Further analysis also revealed that this material system possessed low dielectric constant and ultra-low temperature coefficient of capacitance (TCC) or dielectric constant (TCK). The electrical behavior of these sintered bodies has been systematically correlated with the evolved microstructures. Plausible equivalent circuit elements were extracted using the lumped parameter/complex plane analysis (LP/CPA) and evaluated at various situations.